Evaluation of Zoll Medical's ResQCPR System for cardiopulmonary resuscitation - Debaty, Guillaume; Metzger, Anja; Lurie, Keith (Expert review of medical devices, 2015)
Cardiac arrest remains a leading cause of death, currently affecting more than 250,000 Americans annually. As recommended by the American Heart Association, the current standard of care for patients with an out-of-hospital cardiac arrest (OHCA) includes manual cardiopulmonary resuscitation (S-CPR). Survival with favorable neurological function for all patients following OHCA and treated with S-CPR averages <6%. The ResQCPR System is intended to provide greater circulation to the heart and brain compared with S-CPR, thereby increasing the likelihood of survival. A recent Phase III, multicenter randomized study demonstrated a 50% increase in survival to hospital discharge with favorable neurologic function in subjects with an OHCA of presumed cardiac etiology treated with the ResQCPR System compared with conventional CPR. The ResQCPR System has been recently approved by the FDA as a CPR adjunct to improve the likelihood of survival in adult patients with non-traumatic cardiac arrest.